Exploring The Relationships Among Social Benefits, Online Social Networks Dependency, Satisfaction and Youth's Habit Formation - Tran, Van-Dat; Trang, Huynh Ngoc Doan (International Journal of Informatics and Information Systems, 2018)
Online social network is one of the biggest phenomenon of the Internet, which has attracted many marketers and psychologists to understand social network users' behavior. Recognizing lack of theoretical and empirical attention has been given to this field especially in Vietnam market, this study is conducted to examine the relationships among social benefits, online social network dependency, satisfaction and youth's habit formation in the context of Facebook. The findings of the study of 200 Facebook users indicate that the interrelationship among four factors of social benefits, online social network dependency, satisfaction and habit formation are affected each other. Indeed, online social network dependency among the youth whose age range from 16 to 24 years old is significantly affected by social benefits factor and also lead to the formation of habit. In addition, satisfaction plays a role in determining the habitual use of Facebook. This paper contains a discussion of theoretical and practical implication in marketing and psychology field.